Pengaruh Dosis Pupuk NPK Phonska Plus dan Trichoderma terhadap Pertumbuhan dan Produksi Tanaman Melon (Cucumis melo L.) - Restua Mahardday Situmorang; Kus Hendarto; Yohannes Cahya Ginting; R.A. Diana Widyastuti (Universitas Lampung, 2022)
This study aims to evaluate the growth and production of melons due to the administration of trichoderma sp and the addition of a dose of NPK fertilizer and the interaction of trichoderma sp. with Phonska NPK fertilizer. This research was conducted in the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung from January to March 2021. The treatments were arranged in a 2x4 factorial with 3 replications in a Randomized Block Design (RAK). The first factor is the first factor is trichoderma (without trichoderma and 20 g/plant), the second factor is Phonska NPK fertilizer dose (without NPK, 30 g/plant, 60 g/plant and 90 g/plant). The results showed (1) Application of trichoderma 20 g/plant increased plant stem length (124.45), melon diameter (104.39 mm) higher than without trichoderma application, plant stem length (122.74cm), melon diameter (100, 13 mm), as well as melon weight per plant increased from 666.10 g (without trichoderma application) to 717.05 g (20 g/plant). (2) Application of NPK phonska fertilizer at a dose of 60 g/plant increased plant stem length (125.10 cm), melon diameter (108.70 mm) higher than without NPK application (123.23 cm) (95.82 mm), Likewise, melon weight per plant increased from 649.83 g (without NPK fertilizer) to 748.18 g. (3) Application of trichoderma sp. 20 g/plant in synergy with the application of NPK phonska fertilizer at a dose of 60 g/plant gave the best results based on the variables of plant stem length (127.30 cm), melon diameter (115.00 mm) and melon weight (795.63 g) compared to without application of trichoderma sp and without application of fertilizer the average length of plant stems (123.17 cm), melon diameter (92.77 mm) and melon weight (663.10 g).Keywords : Melon, fertilizer,yield, trichoderma